The truncated non-central negative binomial distribution / Phang Yook Ngor - Phang, Yook Ngor (2004)
Zero truncated distribution arises when the zero class cannot be determined. Several approaches have been used in estimating the parameters of truncated negative binomial and truncated Poisson distribution. In this study, Zinlinkas' optimization routine is used to estimate parameters of the truncated negative binomial distribution. In addition, this paper looks into the zero-truncated non central negative binomial distribution and its application to data fitting. Various estimation methods will be examined and applied to two data sets.